Abdominal Pregnancy: A Case Review - H., Gilcha; H., Kinfemichael; N., Kassa; K., Tadesse (Ethiopian Journal of Reproductive Health, 2018)
Abstract Abdominal pregnancy is a rare type of ectopic pregnancy which occurs in 1 in 10,000 ectopic pregnancies. It has a higher risk of maternal mortality and morbidity. We presented a case of a primigravida mother who presented with a complaint of abdominal pain. Ultrasound result showed abdominal pregnancy and she was operated and macerated fetus and placenta was removed. The pain was resolved and patient was discharged with improvement.